The Crucial Role of Analog Layout in Revolutionizing 5G Connectivity - Kavya Gaddipati, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rapid evolution of 5G technology has positioned analog layout design as a pivotal element in advancing modern telecommunications infrastructure. Through innovative approaches in high-frequency design considerations, circuit optimization techniques, and expert-driven methodologies, analog layout has enabled significant breakthroughs in communication systems. The article of mobile edge computing with vehicular networks, coupled with advancements in mmWave phased array systems, has transformed the landscape of wireless connectivity. Performance enhancements in signal integrity, power efficiency, and thermal management have been achieved through sophisticated layout strategies. Machine learning applications in analog design have revolutionized automation capabilities while maintaining the critical role of human expertise. The implementation of ultra-low voltage techniques and advanced networking protocols has extended the impact beyond traditional telecommunications into Internet of Things and smart city applications. These developments have laid the foundation for next-generation communication systems, enabling enhanced reliability, reduced latency, and improved resource utilization across diverse applications from autonomous vehicles to massive sensor networks.
Keywords: Analog Layout Design; 5G Infrastructure; Millimeter-Wave Communication; Mobile Edge Computing; Ultra-Low Voltage Circuits